Are Mutual Fund Managers Paid for Investment Skill? - Ibert, Markus; Kaniel, Ron; Van Nieuwerburgh, Stijn; Vestman, Roine (Review of Financial Studies, 2018)
Compensation of mutual fund managers is paramount to understanding agency frictions in asset delegation. We collect a unique registry-based dataset on the compensation of Swedish mutual fund managers. We find a concave relationship between pay and revenue, in contrast to how investors compensate the fund company (firm). We also find a surprisingly weak sensitivity of pay to performance, even after accounting for the indirect effects of performance on revenue. Firm-level fixed effects, revenues, and profits add substantial explanatory power for compensation. Received April 25, 2017; editorial decision August 21, 2017 by Editor Matthew Spiegel. Authors have furnished supplementary code, which is available on the Oxford University Press Web site next to the link to the final published paper online.